ANALISA GEOTEKNIK DAN PENANGGULANGAN KELONGSORAN TANGGUL SUNGAI BANJIR KANAL BARAT SEMARANG - Muhammad Afrol Horison; Syarifudin Adi Saputro; Sri Prabandiyani Retno Wardani; Siti Hardiyati (Jurnal Karya Teknik Sipil, 2013)
This undergraduate thesis is about the landslide Geotechnical Analysis and Landslide Handling on theSlope of West Flood Canal – Semarang. Labile land condition result the slope happened slide, one of the slope is gristle slide there are at WF 80 and WF 91. This undergraduate thesis involves conditions which the motions of the soil on the slope because of slope unstability, manual calculation slope stability with Fellinius methods. Landslide simulation was carried out by making a model of slope stratigrafi in accordance with field conditions. Determination of soil types was conducted based on SPT values. Geotechnical analysis using Plaxis finite element software. Plastic and elastic model of Mohr-Coulomb failure criterion was chosen as a model soil. Analysis showed that the most optimum treatment is  install retaining wall and group of  bored pile with a diameter 0,6 meter which is modeled with elastic-plastic beam elements. By using retaining wall + bored pile reinforcement, minimum slope safety factor beincreased and reached 1,363 for WF-80 and safety factor beincreased and reached 1,541 for WF-91.